Differences in drivers’ risk behaviour behind the wheel in relation to road risk perception: Insights from a study on a group of Polish car drivers - Paulina Baran; Piotr Zieliński; Mariusz Krej; Łukasz Dziuda (Heliyon, 2024)
Numerous risky driving behaviours are considered the main causes of road accidents. Meanwhile, a number of studies conducted so far indicate that perceiving a higher risk in a certain behaviour is associated with a lower tendency to engage in that behaviour. Accordingly, the aim of this study was to examine whether there are differences in specific types of risky behaviours behind the wheel in relation to drivers’ perceptions of road risk. The Road Traffic Behaviour Questionnaires KZD and KZD-P were used to evaluate, respectively, different risky behaviours and risk perceptions in road traffic. Two groups of Polish car drivers with similar average KZD scores but significantly different KZD-P scores, i.e., higher vs. lower, were compared. The profiles of the answers were statistically analysed. It was found that drivers with a lower risk perception were far more likely to engage in those behaviours that are the most commonly reported and directly endanger road safety, e.g., speeding and running a red light. Simultaneously, there were several unsafe driving behaviours, e.g., driving without a seatbelt or speaking on a mobile phone while driving, which were taken regardless of risk perception, i.e., even by the drivers who were aware of their riskiness. The results suggest that risk perception is a significant factor in preventing not all types but only selected hazardous behaviours in road traffic. The significance of the findings for traffic safety as well as ideas for further research in this area are discussed.